Efficacy and safety of 100 units of botulinum toxin in the treatment of overactive bladder: a single center experience - Keles, A.; Karakeci, A. (Wiley, 2019)
[Abstract Not Available]
Keywords: incontinence; botulinum; toxin; treatment